Margins, Expenses, and Profits in Retail Hardware Stores (Book). - Meriam, R. S. (The Accounting Review, 1929)
Reviews the book "Margins, Expenses, and Profits in Retail Hardware Stores," by Horace Secrist and J.A. Folse.